El aprendizaje basado en competencias como metodología innovadora en el proceso de enseñanza aprendizaje de la asignatura de Física - García Alvarado, Brillit Mariela (2024)
Competency-based learning (CBL) arises in response to the needs of actual technological, industrial and social sectors and represents an important contribution to experimental sciences. Therefore, this study presents as general objective to describe the relationship of competency-based learning with the teaching and learning of Physics. It is framed in a qualitative approach; documentary design; exploratory scope; documentary review, analytical, deductive and synthetic methods; and card recording technique. The results obtained indicate that the CBL is characterized by adopting holistic: curriculum, activities and strategies, and evaluation system, that promote scientific, technical and humanistic capabilities, both in teachers and students. It is concluded that CBL is a methodology that strengthens the teaching-learning process of Physics and, in this research, its implementation is promoted through a microcurricular planning of the Thermodynamics unit for the second year of the Unified General Baccalaureate. Keywords: Learning, competence, Physics, education.